Exploring the Impact of Social Customer Relationship Management on Customer Loyalty Through Customer Satisfaction as a Mediator in Micro, Small, and Medium Enterprises in Koowe, Asahan Regency - Elly Rahayu; Wan Mariatul Kifti (Jurnal Ekonomi, Bisnis & Entrepreneurship, 2024)
This study aims to examine the impact of Social Customer Relationship Management (SCRM) conducted through social media on customer loyalty, with customer satisfaction acting as a mediator within UMKM KOOWE in Asahan District. The increasing popularity of social media for communication and transactions has become a valuable tool for small and medium-sized enterprises (SMEs) to promote their products, accept orders, and build customer relationships. The choice of social media is often due to its ease of use, cost-effectiveness, and lack of special skills required for operation. One challenge faced by MSMEs KOOWE is measuring customer satisfaction and loyalty, as obtaining a customer database through social media can be difficult. The research employs a descriptive quantitative methodology, analyzing data using Structural Equation Modeling Partial Least Squares (SEM-PLS) with the support of Smart-PLS 3.0 software. Three hypotheses are proposed: First, SCRM significantly influences customer satisfaction; second, customer satisfaction significantly impacts loyalty; and third, SCRM directly affects customer loyalty. The results indicate that all hypotheses are accepted, confirming the positive relationships among these variables. The implications of this research highlight the importance of implementing effective SCRM strategies through social media to enhance customer satisfaction and loyalty, contributing to the growth and sustainability of MSMEs. Businesses can leverage these findings to refine their customer engagement practices for improved performance in a competitive marketplace.